Auditors’ Professional Commitment and Fraud Detection Responsibility: The Importance of Religiosity - Damayanti, Ni Nyoman Sri Rahayu (Fakultas Ekonomi Universitas Kadiri, 2025)
The auditor's obligation to detect fraud is a key factors of fraud disclosure. Strong attachment to professional principles will increase the auditor's sense of responsibility to carry out investigative audits adequately, including detecting fraud. The inconclusive results of previous studies related to the association between professional commitment and fraud detection responsibility, prompt us to propose religiosity as moderating construct. The Triangle Model of Responsibility is used to explain the relationship among professional commitment, religiosity, and auditor responsibility in detecting fraud. This theory state that an individual has high responsibility when there is an obligation to behave in prescribed ways. The respondents are external government auditor who worked in audit board for at least 5 years. Data analysis technique use is SEM-PLS. The results show that the higher the professional commitment, the higher the fraud detection responsibility. On the other hand, religiosity partially moderates the relationship between professional commitment and fraud detection responsibility. This study could be a consideration for audit board to organize auditor training which could improve their sense of professional commitment and also a development activities that could strengthen their level of religiosity.